An Giang University journal of science (An Giang University, 2015)
Contents: Traditional festival in the South west Khmer pagodas - view from value perspective; Buddhism hallmark in settlement of the relation with Champa lands in the reign of Lord Nguyen Phuc Chu; The position, role and service of the Nguyen dynasty and the reason leading to the loss of Viet Nam to the French colonists ay the and of the 19th cetury,...